1994
DOI: 10.1101/gad.8.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Igf2r and Igf2 gene expression in androgenetic, gynogenetic, and parthenogenetic preimplantation mouse embryos: absence of regulation by genomic imprinting.

Abstract: Genomic imprinting in mammals is believed to result from modifications to chromosomes during gametogenesis that inactivate the paternal or maternal allele. The genes encoding the insulin-like growth factor type 2 [IgfZ] and its receptor [lgf2r] are reciprocally imprinted and expressed from the paternal and maternal genomes, respectively, in the fetal and adult mouse. We find that both genes are expressed in androgenetic, gynogenetic, and parthenogenetic preimplantation mouse embryos. These results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
1
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 54 publications
10
71
1
3
Order By: Relevance
“…Genomic imprinting is another important determinant of proper development by monoallelic expression of genes that are regulated during germ-cell and embryo development (23). The genes encoding for insulin-like growth factor type 2 (IGF2) and its receptor (IGF2R) are reciprocally imprinted and expressed from the paternal and maternal genomes, respectively, in the fetal and adult mouse (25). These previous studies indicate that inactivation of imprinted genes occurs postfertilization (25).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic imprinting is another important determinant of proper development by monoallelic expression of genes that are regulated during germ-cell and embryo development (23). The genes encoding for insulin-like growth factor type 2 (IGF2) and its receptor (IGF2R) are reciprocally imprinted and expressed from the paternal and maternal genomes, respectively, in the fetal and adult mouse (25). These previous studies indicate that inactivation of imprinted genes occurs postfertilization (25).…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of the hum an IG F2R gene at earlier stages of development is still unknown. In the mouse, both maternal and paternal Ig f2 r alleles are expressed during preimplantation development (Latham et al, 1994;Szabo and Mann, 1995), indicating that in this species, monoallelic expression is due to secondary in activation of one Ig f2 r gene copy. Along these lines, biallelic expression of the hum an IG F2R gene might result from failing repression of the paternal allele.…”
Section: Cpg 1 Is Completely Unmethylated On Both Parental Igf2r Allementioning
confidence: 99%
“…First evidence that méthylation plays an important role in genomic im printing came from the observation that many transgenes become hypomethylated after passage through the male germline and hypermethylated after passage through the female germline (Surani et a l,, 1988), Analysis of four imprinted genes in the mouse, H19 (Bartolomei et al, 1993;Ferguson-Smith et a l, 1993;Brandeis et al, 1993;Feil et al, 1994), insulinlike growth factor II {Igf2) (Sasaki et a l, 1992;Bran deis et al, 1993;Feil et al, 1994), Igf2 receptor (Igf2r) (Stôger et a lv 1993), and U2afl-rsl (SP2) (Hatada et al, 1995), has revealed that regions within the gene or adjacent to it are methylated in a parent-specific manner, The mouse Igf2r gene is expressed exclusively from the maternally inherited chromosome in fetal and adult tissues (Barlow et al, 1991), with the exception of the head and the brain, where biallelic expression has been observed (Villar and Pedersen, 1994). During preimplantation development, both maternal and pa ternal Ig f2 r alleles are expressed (Latham et al, 1994;Szabô and Mann, 1995), indicating that silencing of the paternal allele is a secondary event. Characterization of the mouse Ig f2 r gene revealed the existence of two distinct CpG islands that show parental-origin-specific méthylation differences.…”
Section: Introductionmentioning
confidence: 99%
“…Such input could be provided by pairing contacts in a critical control region. Biparental contributions, and hence pairing interactions, may be required for imprinting effects on gene expression as well (Latham et al 1994;Mutter et al 1993). Pairing interactions might be particularly influential in cells which contain similar but non-identical homologues ('homeologues').…”
Section: Possible Broader Implications For Vegetative/ Somatic Cellsmentioning
confidence: 99%